An IoT-Based Pill Management System for Elderly - Roumaissa, Boudrali; Rachid, Boudour (Informatica, 2022)
The challenge to guarantee healthy aging has become a major social concern. Due to the cognitive deficits related to age, hectic daily activities, and multiple medications prescriptions, the elders often tend to forget their pills intakes. This has a colossal impact on their health and life. Moreover, the recent pandemic of COVID-19 has accentuated the importance to provide independent and autonomous living for the elderly. This paper presents a pill management system based on IoT intended for aged individuals. The proposed system is a smart pill dispenser associated with a mobile application. The main actors of the system are the patient, the doctor, the pharmacist, and the patient’s caregiver and/or relative, each having restricted access to the system via specific credentials.  The prescription is directly edited on the mobile application by the doctor and the scheduling and filling of the pillbox is done wirelessly by the pharmacist. The reminding of medications intakes in this system is done gradually to help the patient adhere to his/her prescription. First, it notifies the patient about his/her scheduled pill by a mobile notification then via the pill dispenser using LCD, LED, and buzzer. The implemented system also allows the doctor and caregiver to keep a tab of the patient’s intakes. Furthermore, the pill dispenser is featured with a locking mechanism to ensure medication dosage control and prevent drugs abuse. Experiments show that the proposed system is appreciated by the elderly and encourages them to take their pills successfully and safely without causing any disturbance.